A Review on Pharmacology of Tacrolimus In Renal Transplant Patients - Sharma, Anu; Saini, Priyanka; Chhimwal, Jyoti; Sharma, Samiksha; Khan, Mohd. hahid (Asian Journal of Pharmaceutical Research and Development, 2015)
Solid organ transplantation provides a life saving treatment for patients with end stage kidney diseases. But total success after transplantation is hugely dependent on proper course of immunosuppressive therapy. Tacrolimus, a macrolide immunosuppressant agent, is indicated for the prophylaxis of organ rejection in patients receiving allogenic liver or kidney transplantation. The clinical practice still struggles with the shortcomings of the drug: the significant inter- and intraindividual variability of their pharmacokinetics, the unpredictability of their pharmacodynamics effects, as well as complexity of interactions with other agents in transplant recipients. This article briefly reviews the pharmacological aspects of tacrolimus as they relate to the mode of action and pharmacokinetics as well as drug interactions and adverse drug reaction.